Early-life environmental enrichment promotes positive animal welfare for juvenile Atlantic salmon (Salmo salar) in aquaculture research - Pamela M. Prentice; Mauro Chivite Alcalde; Petr Císař; Sonia Rey Planellas (Scientific Reports)
Abstract Early life experiences have long-lasting effects on behaviour and physiology, influencing development of adaptive natural behaviours. Enriching farmed environments encourages expression of natural behaviours in captive fish, promoting positive animal welfare, important for conducting valid and reproducible research and informing better management practices. Using juvenile Atlantic Salmon (Salmo salar), we tested whether provision of environmental enrichment in early life improves welfare. Welfare indicators were measured comparing enriched to non-enriched tanks. Morphological (fin damage and body condition), physiological (plasma cortisol) and behavioural traits (activity, group cohesion, and neophobia) were recorded. Molecular expression of brain mRNA transcripts related to stress response, neuroplasticity and serotonergic system was analysed. Environmental enrichment did not affect morphological welfare indicators, activity, or cortisol. Enriched fish were more cohesive than non-enriched fish, less neophobic, with higher serotonergic turnover, suggesting enrichment mitigates against stress, promoting positive emotional states. Genes related to neuronal development and activity (bdnf and ndf1), cellular stress (hsp90 and hsp70), and serotonin synthesis (tph2) increased in enriched fish following stress, enhancing cognitive function. Our findings suggest early life environmental enrichment is advantageous for positive animal welfare by improving emotional states in captive environments, ensuring animals are free of negative experiences and able to access positive ones.